2014
DOI: 10.1108/mmms-10-2012-0016
|View full text |Cite
|
Sign up to set email alerts
|

FE modeling of creep in linear and non-linear FGM cylinder under internal pressure

Abstract: Purpose -The purpose of this paper is to investigate creep in an internally pressurized thick-walled, closed ends cylinder made of functionally graded composite, having linear and non-linear distribution of reinforcement, using finite element (FE) analysis. Design/methodology/approach -FE-based Abaqus software is used to investigate creep behavior of a functionally graded cylinder. The cylinder is made of composite containing linear and non-linearly varying distributions of reinforcement along the radius. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…The values of creep parameters [ 2 , 24 ] , and are taken as, , and , respectively. Here, for an isotropic cylinder, .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of creep parameters [ 2 , 24 ] , and are taken as, , and , respectively. Here, for an isotropic cylinder, .…”
Section: Resultsmentioning
confidence: 99%
“…The values of creep parameters [2,24] B o , n o and n 3 are taken as, B o = 2.77 × 10 −6 , n o = 3.75 and n 3 = 0.7, respectively. Here, for an isotropic cylinder, F = G = H. The average volume content for SiC p is considered as V avg = 20%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of B 0 , n 0 , u, according to Chen et al, 57 are 2:77 3 10 À16 , 3:75, 0:7, respectively. However, it has been shown that changing these parameters (B r ð Þ, n r ð Þ) has little effect on the strain rate in the Norton equation, 32,51 so in the present work these two parameters are considered constant (B = 4:79 3 10 À22 MPa À6 s À1 , n = 6). 51 By substituting equations (19) and (20) into equation (40), _ e r r i ð Þ and _ e u r i ð Þ are as follows:…”
Section: Creep In Thick-walled Fgm Cylindrical Vesselmentioning
confidence: 93%
“…The most common model for describing the change in the properties of FGM is the application of the power model based on the volume fraction of the material components. In this model, the change in material properties in terms of thickness based on the volume fraction is expressed as follows 51 :…”
Section: Mathematical Formulationsmentioning
confidence: 99%